2010
DOI: 10.1002/asia.201000520
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Chemoenzymatic Approach: One‐Step Syntheses of Monoterpenoid Indole Alkaloids

Abstract: Facile chemoenzymatic syntheses of cytotoxic monoterpenoid indole alkaloids with novel skeletons and multiple chiral centers are described. Synthesis of these alkaloids was achieved by a simple one-step reaction using strictosidine and 12-aza-strictosidine as the key intermediates. Strictosidines were prepared by coupling of secologanin with tryptamine and 7-aza-tryptamine, respectively, using the immobilized recombinant Rauvolfia strictosidine synthase. A detailed stereochemical analysis is presented herein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…In the likely presence of an excess of any primary amine (other nucleophiles have not yet been applied so far) closure of the E ring by a Michael addition takes place to deliver, after borohydride reduction, a diastereomeric mixture of each of the four N-analogous heteroyohimbines. [48,56] Scheme 5. Suggested mechanism of the strictosidine synthase catalyzed Pictet-Spengler reaction between tryptamine and secologanin, which generates the biosynthetic monoterpenoid indole alkaloid precursor 3a(S)-strictosidine enantioselectively.…”
Section: Str-based Biomimetic Approach To Heteroyohimbinesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the likely presence of an excess of any primary amine (other nucleophiles have not yet been applied so far) closure of the E ring by a Michael addition takes place to deliver, after borohydride reduction, a diastereomeric mixture of each of the four N-analogous heteroyohimbines. [48,56] Scheme 5. Suggested mechanism of the strictosidine synthase catalyzed Pictet-Spengler reaction between tryptamine and secologanin, which generates the biosynthetic monoterpenoid indole alkaloid precursor 3a(S)-strictosidine enantioselectively.…”
Section: Str-based Biomimetic Approach To Heteroyohimbinesmentioning
confidence: 99%
“…Following optimized overexpression, [57] STR1 was used for the synthesis of azastrictosidine from 7-azatryptamine (Scheme 7). [56,58] Moreover, azastrictosidine has been used for the simple one-step chemical synthesis of a previously unknown lactam of azastrictosidine and for azanacycline under basic and acidic conditions, respectively. [56] Modification of the tryptamine unit by introducing a nitrogen atom in different positions should, therefore, ultimately result in a range of diverse and novel azaindole alkaloids.…”
Section: Str-based Biomimetic Approach To Heteroyohimbinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter serves as a central precursor of naturally occurring, biologically active indole alkaloids, thus the enzyme is located in the biosynthetic pathways at the central branching point of more than 2000 monoterpenoid indole alkaloids in higher plants, including some possessing extraordinary medicinal and therapeutic value 8. In general STRs have been reported to show a narrow substrate spectrum with respect to the aldehyde reactant, transforming only secologanin and close derivatives in most cases;7, 9 to the best of our knowledge, only one report indicated that simple non‐natural aliphatic aldehydes might also be accepted 10. Therefore, our aim was to investigate the substrate tolerance of STRs for non‐natural aldehydes.…”
mentioning
confidence: 99%
“…Enzyme-catalyzed biosynthesis and chemo-enzymatic synthesis of pharmacologically active, plant-derived monoterpenoid indole alkaloids have attracted interest in recent years (1)(2)(3)(4)(5). A detailed knowledge of the participating enzymes is an indispensable requirement for further progress in this field.…”
mentioning
confidence: 99%